2023
DOI: 10.1101/2023.04.16.537068
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Inter-generational nuclear crosstalk links the control of gene expression to programmed genome rearrangements during theParameciumsexual cycle

Abstract: Multinucleate cells are found in many eukaryotes, but how multiple nuclei coordinate their functions is still poorly understood. In the cytoplasm of the ciliateParamecium tetraurelia, two micronuclei (MIC) serving sexual reproduction coexist with a somatic macronucleus (MAC) dedicated to gene expression. During sexual processes, the MAC is progressively destroyed while still ensuring transcription and new MACs develop from copies of the zygotic MIC. Several gene clusters are successively induced and switched o… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 65 publications
0
3
0
Order By: Relevance
“…Along with strong inhibition of iesRNAs, PTIWI10/11 expression was abolished by the ICOP KDs. As these genes are transcribed in the developing MAC, the loss of PTIWI10/11 expression could either be due to the retention of an IES in their promoter region or to nonsense-mediated decay (NMD) of mRNA triggered by IES retention in the CDS (Bazin-Gélis et al 2023;Sandoval et al 2014;Furrer et al 2017). sRNA sequencing also revealed that the MAC-specific scnRNAs are elevated in ICOP1/2-KD compared to the control (Fig 6H).…”
Section: Discussionmentioning
confidence: 97%
“…Along with strong inhibition of iesRNAs, PTIWI10/11 expression was abolished by the ICOP KDs. As these genes are transcribed in the developing MAC, the loss of PTIWI10/11 expression could either be due to the retention of an IES in their promoter region or to nonsense-mediated decay (NMD) of mRNA triggered by IES retention in the CDS (Bazin-Gélis et al 2023;Sandoval et al 2014;Furrer et al 2017). sRNA sequencing also revealed that the MAC-specific scnRNAs are elevated in ICOP1/2-KD compared to the control (Fig 6H).…”
Section: Discussionmentioning
confidence: 97%
“…We found that these genes are indeed deregulated upon GTSF1 KD (Figure S2). Focusing on the 628 developmental genes that are up-regulated upon KD of the elimination machinery (Pgm, Ku80 and Xrcc4) (Bazin-Gélis et al, 2023), we found that depletion of either Gtsf1 or Ezl1 also affects the expression of these genes (Figure S2). Thus, Gtsf1 depletion, as that of other proteins essential for DNA elimination, results in the deregulation of a subset of developmental genes, and this is likely a response to defective IES excision in the new MAC.…”
Section: Resultsmentioning
confidence: 99%
“…At the subsequent stages, DevPF1 - and DevPF2 -KD affected similar genes. Either, the changes are nonspecific to the DevPF -KDs and result from the proposed nuclear crosstalk to adjust transcription levels to accommodate for failed IES excision (Bazin-Gélis et al, 2023) or they are specific to the DevPF -KDs and both paralogs exhibit similar functions in the regulation of gene expression. Interestingly, differential expression was observed at the “early” time point (Fig.…”
Section: Discussionmentioning
confidence: 99%